Simulating a metallicity-dependent initial mass function: consequences for feedback and chemical abundances - Gutcke, Thales A.; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Observational and theoretical arguments increasingly suggest that the initial mass function (IMF) of stars may depend systematically on environment,